Rethinking Contemporary Qur’anic Epistemology: Neurotheology, Double Consciousness, and Non-Arabcentric Hadith Traditions - Syafii, Muhammad Hisyam; Azhari , Husain; Alaldaya, Rudyn; Amirudin , Amirudin (Universitas Islam Tribakti Lirboyo Kediri, 2026)
This study investigates the neurotheological reconstruction of Qur'anic foundations undertaken by Indonesian muhaddith operating within non-Arabcentric Islamic intellectual traditions, examining how these scholars negotiate classical hadith methodology alongside indigenous Indonesian spiritual epistemology and contemporary cognitive neuroscience. Employing a qualitative interpretive methodology integrating in-depth semi-structured interviews, critical discourse analysis of institutional texts, and ethnographic observation within Indonesian Islamic learning communities, this study systematically documents the epistemological strategies through which Indonesian muhaddith reconstruct the neurological and psychological dimensions of Qur'anic engagement beyond Arab-normative hermeneutical frameworks. The findings reveal that Indonesian muhaddith construct a distinctive form of epistemological double consciousness, theorize the collective neurotheological dimensions of Qur'anic recitation practice, and reconstruct the classical concept of nafs through the convergence of hadith anthropology, indigenous Javanese spiritual epistemology, and contemporary psychological science. The novelty of this study lies in its theorization of non-Arabcentric Islamic scholarship as a productive site of neurotheological innovation, demonstrating that cultural and cognitive diversity within global Muslim intellectual traditions constitutes an epistemological resource rather than a deviation from normative Islamic hermeneutical standards. Contribution: This study contributes by advancing neurotheological approaches in Islamic studies, repositioning non-Arabcentric scholarship as a locus of epistemological innovation, and offering an integrative framework linking hadith studies, Islamic anthropology, and cognitive science to explain the embodied and socially mediated dimensions of Qur’anic engagement.